Global Exposition of Wildlife Management - Stephen Lameed, Gbolagade A. (IntechOpen, 2017)
The book, Global Exposition of Wildlife Management, covers five research topics connected to wildlife management. From conservation and domestication of species from the wild, the socioeconomic importance of wildlife to Tuberculosis within wildlife species as an emerging health threat for both wildlife and humans. Topics presented also discuss bush-meat utilization and its impact on biodiversity conservation, community forestry management and its role in biodiversity conservation, food and feeding ecology, urban forestry, and integrated island management for ecologically sensitive areas. This book also presents wildlife conservation research using a public aquarium as a case study. Each chapter gives special reference to the prevailing problems in wildlife conservation and hopes to provide possible solutions.